Clinical outcomes of simultaneous phototherapeutic keratectomy and photoastigmatic keratectomy - Kazutaka Kamiya (Nature Portfolio, 2021)
Abstract This study was aimed to assess the outcomes of simultaneous phototherapeutic keratectomy (PTK) and photoastigmatic keratectomy (PAK), with special attention to astigmatic correction. We comprised 70 eyes of 70 patients who underwent simultaneous PTK and PAK in patients having granular corneal dystrophy and band keratopathy with refractive astigmatism of 1 diopter (D) or more. Preoperatively and 6 months postoperatively, we assessed corrected uncorrected distance visual acuity (UDVA), distance visual acuity (CDVA), manifest spherical equivalent, refractive astigmatism, corneal astigmatism, and higher-order aberrations (HOAs). LogMAR CDVA significantly improved, from 0.27 ± 0.27 preoperatively, to 0.13 ± 0.21 postoperatively (Paired t test, p < 0.001). LogMAR UDVA also significantly improved, from 0.70 ± 0.32 preoperatively, to 0.57 ± 0.41 postoperatively (p = 0.043). Refractive astigmatism significantly decreased, from 2.12 ± 0.95 D preoperatively, to 0.89 ± 0.81 D postoperatively (p < 0.001). Corneal astigmatism also significantly decreased, from 2.17 ± 0.90 D preoperatively, to 1.08 ± 0.71 D postoperatively (p < 0.001). Corneal HOAs did not significantly change, from 0.54 ± 0.30 µm preoperatively, to 0.48 ± 0.20 µm postoperatively (p = 0.140). No significant complications occurred in any eye. Simultaneous PTK and PAK treatment is effective not only for improving visual acuity, but also for reducing astigmatism.